Pemberdayaan Psikologis dan Intensi Turnover Karyawan Milenial di Indonesia: Peran Keterikatan Kerja sebagai Mediator - Rizqi Zulfa Qatrunnada (Universitas Ciputra Surabaya, 2023)
This study aims to examine the effect of psychological empowerment on turnover intention mediated by work engagement in Millennial employees in Indonesia. This research is a quantitative study with a cross-sectional study design involving 99 Millennial employees in Indonesia. The sampling technique in this study was accidental sampling by distributing questionnaires online. Hayes mediation analysis was used to examine the role of mediation in this study. The results of this study indicate that psychological empowerment affects turnover intention by being mediated by work engagement (F(2,96)= 10.5924, p=0.0001). Furthermore, it is known that there is a positive regression of psychological empowerment to work engagement (β = 0.63, SE= 0.08, p < .001) and a negative regression to turnover intention (β= -0.19, SE= 0.06, p= .0016). It means that increasing the psychological empowerment felt by employees enhances an employee's work engagement, and in turn, reducing the intensity of employees leaving work. The implications of this research in detail will be discussed further.